The Tulumbe! Partnership: a case study in developing a community-led research agenda to address HIV among African immigrants in the United States - Nnaji, Chioma; Anyango, Lorraine; Bova, Carol; Kiggundu, Frederick; Mbao, Mbita; Oloyede, Dara; Omotola, Ayomide (Frontiers in Public Health, 2024)
Grassroots, community organizations are trusted resources within communities, which puts them in an ideal position to effectively engage individuals impacted by health inequities in defining meaningful research priorities. A community-centered approach to HIV research is critical for African immigrants living in the United States, who experience stigma and other socio-structural barriers to HIV prevention, care, and research engagement. Supporting community organizations with financial resources and capacity building activities to lead the development of research agendas ensures better alignment with community interests and fosters sustainability. We developed a community-initiated and -led research engagement project—Tulumbe!, which prioritized community leadership in all project activities. Community forums, health care provider and community questionnaires, interviews, and report-back sessions were held to examine the research interests and health concerns voiced by African immigrants. The iterative, community-led engagement process of more than 200 African immigrants, health providers, and researchers resulted in a community-defined research agenda with six areas of focus: family communication; self-efficacy for African immigrant women; deconstructing masculinity for African immigrant men; sexual health education for African immigrant youth; HIV stigma; and health literacy. Time, resources, and flexibility are needed to develop a viable community-led research partnership. Investing in community leadership not only produced a patient-centered research agenda but also led to community ownership of the process and results; thus, all partners were committed to sustaining the work.